2023
DOI: 10.1037/tra0001311
|View full text |Cite
|
Sign up to set email alerts
|

Prospective examination of psychological trauma among adolescents during the COVID-19 pandemic.

Abstract: Objective: This longitudinal study investigated the predictors of and changes in psychological trauma during the COVID-19 pandemic. Method: Participants included 236 adolescents (130 males; M age = 16.74 years in spring 2020; 49.6% diagnosed with attention-deficit hyperactivity disorder; 16.1% diagnosed with an anxiety or depressive disorder) in the United States who completed online questionnaires at four timepoints (spring 2020, summer 2020, fall 2020, spring 2021). Results: Repeated measures ANOVA showed th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 58 publications
(74 reference statements)
0
3
0
Order By: Relevance
“…In the recent literature, it is possible to come across studies suggesting that timely handling of mental health burdens by using simple, self-administered screening tools will prevent dire consequences in the future [38]. The most recent studies on adolescents in the literature were reviewed and it was found that 20% of the adolescents experienced psychological trauma symptoms during the COVID-19 epidemic; It was emphasized that there is a critical need to provide mental health services such as school-based services to adolescents to reduce the longterm negative psychological impact of the pandemic [39]. In our opinion, mental health services may need to be strengthened to alleviate the long-term effects.…”
Section: Discussionmentioning
confidence: 99%
“…In the recent literature, it is possible to come across studies suggesting that timely handling of mental health burdens by using simple, self-administered screening tools will prevent dire consequences in the future [38]. The most recent studies on adolescents in the literature were reviewed and it was found that 20% of the adolescents experienced psychological trauma symptoms during the COVID-19 epidemic; It was emphasized that there is a critical need to provide mental health services such as school-based services to adolescents to reduce the longterm negative psychological impact of the pandemic [39]. In our opinion, mental health services may need to be strengthened to alleviate the long-term effects.…”
Section: Discussionmentioning
confidence: 99%
“…Research on trauma symptoms during COVID-19 has almost exclusively focused on adults (Lewis et al, 2022), and up to now there is only one study available based on parent-reported traumatic symptoms in children (Ma et al, 2021). The COVID-19 pandemic may disproportionately affect children, as children often suddenly lose essential resilience factors, namely the support of parents, friends, neighbours and the social infrastructure that is normally in place to ensure their safety and provide assistance (A. Danese & Smith, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Although the pandemic may have changed all children's lives, there might be children who are especially at risk to experience the harmful effects of this pandemic. Therefore, it is important to identify children that are particularly at risk for experiencing a high level of trauma to stop the process to develop further into psychopathology.Research on trauma symptoms during COVID-19 has almost exclusively focused on adults (Lewis et al, 2022), and up to now there is only one study available based on parent-reported traumatic symptoms in children (Ma et al, 2021). The COVID-19 pandemic may disproportionately affect children, as children often suddenly lose essential resilience factors, namely the support of parents, friends, neighbours and the social infrastructure that is normally in place to ensure their safety and provide assistance (A. Danese & Smith, 2020).There is much need for hearing the voices of children experiencing trauma by using children's self-reports.Clinicians and other practitioners rely mainly on symptoms of mental health reported by parents, teachers or other caregivers rather than by children self-reports (…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The protracted duration of the pandemic and the consequent implementation of lockdown measures have elicited apprehensions regarding the adverse effects on the mental well-being of adolescents, specifically about the closure of schools and disturbances to their daily schedules (Guessoum et al, 2020). Moreover, a significant number of adolescents have exhibited psychological trauma symptoms in connection with the pandemic, underscoring the imperative to tackle the mental health consequences of this crisis (Lewis et al, 2023). School closures during the pandemic have caused chronobiological changes in adolescents, providing valuable information about how the pandemic has affected their daily schedules and routines .…”
Section: Introductionmentioning
confidence: 99%